2011
DOI: 10.3329/taj.v15i1.8378
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity after hysterectomy

Abstract: Fifty-four women were examined 3 to 6 months after hysterectomy, with General Health Questionnaire and DSM-IV to find out the psychiatric morbidity. 38.8% women had psychiatric disorder, which is higher than general population. Depressive disorder and generalized anxiety disorder were the common psychiatric diagnosis. To minimize the psychiatric complications, it was suggested that the women should undergo counseling before and after the operation to minimize the psychiatric complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This was highly significant difference in hysterectomized women as compared to control group (p<0.0001) ( Table 5). 13,15 So the present study finding was consistent with the findings of other studies. Regarding the parity, current study showed that, 98.6% respondents of the hysterectomized group were multiparous.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This was highly significant difference in hysterectomized women as compared to control group (p<0.0001) ( Table 5). 13,15 So the present study finding was consistent with the findings of other studies. Regarding the parity, current study showed that, 98.6% respondents of the hysterectomized group were multiparous.…”
Section: Resultssupporting
confidence: 93%
“…In this regards, another Bangladeshi study showed that 86.96% respondents were multiparous and an Indian study showed that 74% respondents were multiparous. 13,15 This preponderance of multiparity could be due to the fact that before completion the family (at least two children) it was hardly tried by the gynecologist to manage the adverse gynecological condition conservatively. Consequently patient and her family member might also refuse to give consent before completion her family.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations